2023
DOI: 10.1186/s12864-023-09480-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pedigree and genomic inbreeding coefficients, and inbreeding depression of reproductive traits in Japanese Black cattle

Abstract: Background Pedigree-based inbreeding coefficients have been generally included in statistical models for genetic evaluation of Japanese Black cattle. The use of genomic data is expected to provide precise assessment of inbreeding level and depression. Recently, many measures have been used for genome-based inbreeding coefficients; however, with no consensus on which is the most appropriate. Therefore, we compared the pedigree- ($${F}_{PED}$$ F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…By analyzing the phenotypes of a large simulated pedigreed polygamous population with strong family structure as well as subsets of the 1,000 genomes project ( 33 ), we demonstrated that, despite population or family structure, ID strength can be efficiently estimated if the data are analyzed with a mixed model including the genomic relationships among individuals as a random effect. While the use of a relationship matrix as a random factor in mixed models for quantitative genetics analyses is standard ( 34 ), and GRMs have been used for the estimation of heritability ( 18 , 35 37 ) and in GWAS ( 18 , 37 41 ) for a long time, it is seldom used to quantify ID [see McQuillan et al ( 42 ) for a notable exception; we did not discover any follow-up papers using a similar approach until Nishio et al ( 43 ) who used the GCTA based GRM in 2023, although Stoffel et al ( 44 ) use a model with breeding values as random effects]. We evaluate the ability of the LMM approach (including different GRMs) to quantify ID and compare it to the classical LM.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the phenotypes of a large simulated pedigreed polygamous population with strong family structure as well as subsets of the 1,000 genomes project ( 33 ), we demonstrated that, despite population or family structure, ID strength can be efficiently estimated if the data are analyzed with a mixed model including the genomic relationships among individuals as a random effect. While the use of a relationship matrix as a random factor in mixed models for quantitative genetics analyses is standard ( 34 ), and GRMs have been used for the estimation of heritability ( 18 , 35 37 ) and in GWAS ( 18 , 37 41 ) for a long time, it is seldom used to quantify ID [see McQuillan et al ( 42 ) for a notable exception; we did not discover any follow-up papers using a similar approach until Nishio et al ( 43 ) who used the GCTA based GRM in 2023, although Stoffel et al ( 44 ) use a model with breeding values as random effects]. We evaluate the ability of the LMM approach (including different GRMs) to quantify ID and compare it to the classical LM.…”
Section: Discussionmentioning
confidence: 99%
“…The level of inbreeding in a population is an important parameter for monitoring its genetic diversity and its management. High levels of inbreeding cause inbreeding depression and should be avoided in farm animals [ 49 ]. Moreover, increasing inbreeding is associated with negative effects on the production and reproductive characteristics of dairy cows [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of genomic inbreeding coefficients using ROH can be utilized to assess inbreeding in a species or population. A significant advantage of estimating these genomic inbreeding coefficients lies in the availability of chromosomal inbreeding coefficients [ 42 ]. Long ROHs reflect recent generations of inbreeding, while short ROHs indicate more distant generations of inbreeding.…”
Section: Discussionmentioning
confidence: 99%